More or More of the Same: Ownership Concentration and Media Diversity in Egypt. (October 2021) - Badr, Zahraa
The Egyptian media has witnessed various changes in the ownership spectrum after the 2011 revolution. To explore this evolution, and through the Habermasian lens, this study examined ownership concentration in the 2019 media sphere in Egypt by mapping media outlets and their owners. It also investigated the relationship between this concentration and content diversity in a sample of print outlets in the first quarter of 2019. Three patterns of ownership concentration in the Egyptian media were identified: concentrated state ownership, concentrated private ownership, and not concentrated private ownership. Based on these findings, I argue that the media sphere in Egypt is dominated by a few gatekeepers, mostly the state, that influence content diversity and jeopardize the democratic public sphere in postrevolution Egypt.